Annually Resolved Propagation of CFCs and SF 6 in the Global Ocean Over Eight Decades - Cimoli, L; Gebbie, G; Purkey, SG; Smethie, WM (American Geophysical Union (AGU), 2023)
Abstract Oceanic transient tracers, such as chlorofluorocarbons (CFCs) and sulfur‐hexafluoride (SF 6 ), trace the propagation of intermediate‐to‐abyssal water masses in the ocean interior. Their temporal and spatial sparsity, however, has limited their utility in quantifying the global ocean circulation and its decadal variability. The Time‐Correction Method (TCM) presented here is a new approach to leverage the available CFCs and SF 6 observations to solve for the Green's functions (GFs) describing the steady‐state transport from the surface to the ocean interior. From the GFs, we reconstruct global tracer concentrations (and associated uncertainties) in the ocean interior at annual resolution (1940–2021). The spatial resolution includes 50 neutral density levels that span the water column along World Ocean Circulation Experiment/Global Ocean Ship‐Based Hydrographic Investigations Program lines. The reconstructed tracer concentrations return a global view of CFCs and SF 6 spreading into new regions of the interior ocean, such as the deep north‐western Pacific. For example, they capture the southward spreading and equatorial recirculation of distinct North Atlantic Deep Water components, and the spreading of CFC‐rich Antarctic Bottom Water out of the Southern Ocean and into the North Pacific, East Indian, and West Atlantic. The reconstructed tracer concentrations fit the data in most locations (∼75%), indicating that a steady‐state circulation holds for the most part. Discrepancies between the reconstructed and observed concentrations offer insight into ventilation rate changes on decadal timescales. As an example, we infer decadal changes in Subantartic Mode Water (SAMW) and find an increase in SAMW ventilation from 1992 to 2014, highlighting the skill of the TCM in leveraging the sparse tracer observations.